Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s12144-022-03514-z
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of autism: exploring experiences of males diagnosed with autism in adulthood

Abstract: Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder associated with qualitative impairments in social interaction, social communication and restricted, repetitive behaviour (American Psychiatric Association, 2013). Symptoms of ASD are first evident in infancy and childhood. However, individuals presenting with less overt ASD symptomatology may only be diagnosed in adulthood, when the expectation of independence and productivity results in a growing crisis for the individual. This study ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Across the studies, the sample size ranged from eight (Atherton et al, 2022) to 77 participants (Lewis, 2016). All studies used a mixed-gender sample except for Leedham et al, (2020) who only included females and Lupindo et al, (2022) who only included males. The mean age of participants ranged from 29.8 years (Atherton et al, 2022) to 60.38 years (Hickey et al, 2018) and the mean age at diagnosis ranged from 34.75 years (Lupindo et al, 2022) to 49.19 years (Lilley et al, 2021.…”
Section: Study Design and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Across the studies, the sample size ranged from eight (Atherton et al, 2022) to 77 participants (Lewis, 2016). All studies used a mixed-gender sample except for Leedham et al, (2020) who only included females and Lupindo et al, (2022) who only included males. The mean age of participants ranged from 29.8 years (Atherton et al, 2022) to 60.38 years (Hickey et al, 2018) and the mean age at diagnosis ranged from 34.75 years (Lupindo et al, 2022) to 49.19 years (Lilley et al, 2021.…”
Section: Study Design and Qualitymentioning
confidence: 99%
“…Not describing how researchers' subjectivity was managed, reduces the credibility of results. Only the papers by Lupindo et al, (2022) and Stagg & Belcher, (2019) provided a reflexive comment on their positionality. However, other papers did describe some reflexive techniques (Leedham et al, 2020;Lewis, 2016;Lilley et al, 2021;Punshon et al, 2009).…”
Section: Study Design and Qualitymentioning
confidence: 99%
“…In girls, late diagnosis would also be caused by the development of compensatory measures, such as the act of observing and imitating neurotypical children. [ 18 , 19 ] This may also have influenced the fact that we found a significantly lower mean age at diagnosis in boys than in girls in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have suggested that autistic girls often go undiagnosed (Dworzynski et al., 2012, p. 793; Petrou et al., 2018, p. 32). This can lead to missed opportunities for early intervention and support regarding social communication and interaction difficulties (Lupindo et al., 2022); a common area of need for autistic individuals (Knott et al., 2006, p. 609). This in turn increases the risk of mental health problems, such as anxiety (Bargiela et al., 2016; Rae & Hershey, 2019, p. 113).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact on mental health cause by SCIDs is particularly true for late‐diagnosed autistic individuals (Lupindo et al., 2022). However, much of this research relies on small sample sizes with a bias towards autistic males; in White and Roberson‐Nay's (2009) sample, 18 of the 20 participants were male.…”
Section: Introductionmentioning
confidence: 99%